IDENTIFICATION OF EPO-Fс FUSION PROTEIN BY MEANS OF POLYACRYLAMIDE GEL-ELECTROPHORESIS WITH ISOELECTROFOCUSING (IEF-PAGE)AND IN PRESENCE OF SODIUM DODECYLSULPHATE (SDS-PAGE)/ LAUROYLSARCOSINATE (SAR-PAGE) FOR THE PURPOSE OF ANTI-DOPING CONTROL - P. V. Postnikov; G. I. Krotov; Yu. A. Efimova; M. A. Dikunets (Тонкие химические технологии)
The article is devoted to develop of an approach for the identification of new stimulator of ematopoiesis, EPO-Fc fusion protein, which is banned by the World Anti-doping Agency (WADA) to use by athletes since it has become doping. Existing methods of qualitative determination of this substances in routine practice of antidoping laboratories such as polyacrylamide gelelectrophoresis in presence of sodium dodecylsulphate (SDS-PAGE) or lauroylsarcosinate (SARPAGE) are insufficiently specific. The article shows the principal possibility of identification of EPO-Fc fusion protein by means of IEF-PAGE in carrier ampholyte-based gels with a pH range 2-6 after Fc-fragment removal via fermentative hydrolysis.It has been shown that the removing of the crystallizable fragment leads to decrease of molecular weight of whole hybrid molecule and to increase its electrophoretic mobility that allows to detect this banned substances with high specificity by existing methods. During the study the enzyme for hydrolytic cleavage and optimum conditions of hydrolysis of EPO-Fc in serum samples were selected.